Sufism Social Education in Government Policy Related to the Orientation of the MajelisTaklim in Indonesia - M. Aba Yazid; Athoillah Islamy; Zulihi (Journal of Islamic Civilization, 2023)
Intolerance, radicalism, and terrorism in the name of Islam remain national security problems in Indonesia. This emphasizes the synergy of perfective efforts between the government and Muslims through Islamic educational and social activities. Through a normative-philosophical approach, this qualitative study in the form of a literature review intends to identify and explore the content of Sufism values in the orientation of the MajelisTaklim as stated in Article 4 of the Minister of Religious Affairs Regulation no. 29 of 2019. Data collection through documentation and data analysis using the reduction, presentation, and verification stages. The results of this study concluded that there is a content of Sufism values in the educational orientation of the MajelisTaklim in Indonesia, including the value of mahabbah in the orientation of forming the character of the humanist personality of Muslims, the value of futuwwah in the orientation of forming the personality of pluralist Muslims, the value of itsar in the orientation of forming the personality of nationalist Muslims. The theoretical implications of this study show that the values of socio-sufistic teachings can be integrated with government political policies related to the orientation of non-formal Islamic education in Indonesia, as well as Islamic education activities through the MajelisTaklim.